Can costochondral grafts fulfil ramus-condyle unit reconstruction goals in children with temporomandibular joint ankylosis?. Issue 2 (February 2021) - Lakshmanan, S.; Roychoudhury, A.; Bhutia, O.; Yadav, R.; Bhatt, K.; Pandey, R.M.
Abstract: The purpose of this study was to analyse whether costochondral grafts (CCG) fulfil temporomandibular joint (TMJ) reconstructive goals in children with TMJ ankylosis. A total of 23 patients (12 male, 11 female, aged 3–16 years) with unilateral or bilateral TMJ ankylosis operated on between January 2014 to April 2018 were included in the study. Maximal incisal opening (MIO), frequency of reankylosis, and growth of CCG, were evaluated at one month and six months for one year, and after that once yearly. Mouth opening changes with time were assessed by the Friedman test and growth was compared at follow up and analysed using the paired t test. Mean (range) follow up was 18 (12–48) months. Study results revealed follow up MIO at 12 months was highly significant ( p  = 0.001). Out of 27 CCG studied, only one graft had undergone re-ankylosis. Based on the predetermined criteria using condylion to gnathion (Co–Gn) measurement in the posteroanterior cephalogram, CCG were categorised into optimum, sub-optimum, and overgrowth. However, long-standing TMJ ankylosis cases still displayed mandibular asymmetry at the end of the study, even with "optimal growth" radiographically. Overall comparison between the immediate postoperative and last follow up Co-Gn measurements in either unilateral or bilateral cases was not significant. CCG with functional matrix maintained the growth of the mandible and MIO in TMJ ankylosis. It can be concluded that CCG partially fulfils reconstructive goals; however, patients need to be followed up till the end of puberty for a substantive conclusion.